Gambaran Darah Merah Ayam Buras yang Terinfeksi Leucocytozoon - PASTI APSARI, IDA AYU; SURAGA ARTA, I MADE (Jurnal Veteriner, 2010)
Sixty four samples from female and male local chickens in high and low attitude areas of Bali wereexamined for Leucocytozoon infection. Erytrocyte count, haemoglobin level and packed cell volume (PCV)were examined. Data obtained from this study was analyzed by Wilcoxon Mann Whitney Test. The resultshowed that no significant difference was observed on erytrocyte, haemoglobin and PCV values betweeninfected (2,48 x 106/mm; 9,36g/dl; and 33,62% respectively) and uninfected (2,56x106/mm3; 9,47g/dl and34,28% respectively). A significant difference was however observed on the erythrocyte count between malechickens in higher area (2,60x106/mm3) and female in lower area (2,59x106/mm3). No significant differencewas observed on haemoglobin and PCV between male chickens in higher area (9,35g/dl & 34,62% and9,56g/dl & 34,75% respectively) and female chickens in lower area (9,38g/dl & 32,63% and 9,16g/dl &32,5% rspectively).
Keywords: Leucocytozoon, erytrocyte, haemoglobin, Packed cell volume (PCV)